Advanced motif programming techniques - George, Alistair (Prentice Hall, 1994)
This book is aimed at the developer who is building Motif user interfaces for real applications. It complements the toolkit documentation by explaining not only what features are available, but also how and why they should be used. You can read this book from cover to cover to gain a deeper understanding of Motif and the surrounding technologies, or you can dip into it to find a solution to a particular problem or an explanation of a feature. Part one covers the toolkit itself, detailing interesting resources and giving examples of use for each of the widgets. Part two concentrates on techniques that are used in conjunction with the toolkit to add capability to your user interfaces. Features: extensive drag and drop examples, basic X drawing techniques, handling application scrolling, hints and tips for form layout, and simple internationalisation.